(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2014)
The museum has always been open to virtuality, to mimesis, since the objects it collects are often images. But with the competition from modern spectacles, the museum was quickly confronted with a broader virtuality, that of immersion, which places the viewer not in front of the image, but in the image. Obviously, the immersive aesthetic is not ideally suited to the museum’s education, cultural and cultural mandate. The long and complex history of the relationship between the museum and cinema – which culminated in the “cinéma d’exposition” – clearly demonstrates this. The museum’s recent interest in mixed-reality games, which echoes the use of the Internet and video games by mass culture, has renewed this tension. We will test these hypotheses in examining Uncle Roy All Around You (2003), an exemplary game involving street-players and online players collaborating in the search for a mysterious missing person, which was designed by Blast Theory and which premiered at the Institute of Contemporary Arts in London.